The Influence of Marketing Information Systems and Product Difference on Consumer Purchase Decisions PT Kemasindo Fast - Mila Asmawiani Okta; Chon Cho Reynols Manday (Jurnal Mantik, 2022)
PT Kemasindo Cepat  Medan is: one of the main distribution companies for Honda cars that markets Honda cars only for the North Sumatra and Nanggroe Aceh Darussalam regions. Problems at PT Kemasindo Cepat  is in marketing products through sales opening channels available at several centers or through reference channels from one party to another, for this proves that the company is in developing a marketing information system within a limited company. The purpose of this study was to determine and analyze the effect of Marketing Information Systems and Product Differentiation on Consumer Purchase Decisions of PT. Deli Kencana Palace, Medan. The method used in this research is a survey approach, this type of research is descriptive quantitative. The number of population and samples in this study were 38 people. The sampling technique used was saturated sampling technique. Methods of collecting data were interviews, documentation studies, questionnaires and literature studies. Variables were measured using a Likert scale. The data analysis model used to answer the hypothesis is multiple linear regression analysis. The results showed that simultaneously there was a positive and significant influence between the variables of Marketing Information System and Product Differentiation on Consumer Purchase Decisions of PT. Deli Kencana Palace, Medan. Partially there is a positive and significant influence between the variables of Marketing Information System and Product Differentiation on Consumer Purchase Decisions of PT. Deli Kencana Palace, Medan.